Productivity Analysis: A Micro-to-Macro Perspective - Bo Carlsson (The Research Institute of Industrial Economics (IUI), 1987)
This paper raises several issues concerning productivity analysis. An attempt is made to demonstrate the usefulness of a micro-based approach to productivity analysis which challenges some basic assumptions of conventional analyses based on aggregate production functions. With the help of a micro- (firm-)based macro simulation model it is shown if there are important differences among firms in economic competence, here represented by efficiency and investment behavior, the relationships between investment, productivity, and economic growth are much more complex and unpredictable than commonly assumed . The rate of technological progress as measured by the rate of change in best-practice technology seems to be less important than the elimination of inefficiency by closure of firms and/or by firms moving closer to their respective production frontiers. It is also shown that the conditions which determine firm borrowing for investment (involving their interpretation of past profitability and expectations based on current capacity utilization) are more important for productivity and economic growth than the total amount invested. In other words, it matters less how much is invested than who does the investing, and under what incentives. The implication for productivity analysis is that unless diversity among economic units is taken into account, the results are likely to continue to be inconclusive. What is needed is much more of an integration of micro and macro theory than has been accomplished thus far. In particular, economic competence must be included. The paper also tries to put productivity in the proper perspective, not as an object in and of itself but rather as a partial measure, at best, of economic performance at any level within the economy.
Keywords: C53; D22; D24; G11; O33; 330; Productivity analysis; micro-to-macro model; simulation; investment; economic growth; technological progress; Arbeitsproduktivität; Technischer Fortschritt; Theorie; Schweden